(untitled) (African Journal of Biomedical Research, 2023)
Malaria is a foremost preventable cause of death and a major public health concern. Inadequate knowledge of malaria management in pediatrics among future pharmacists could affect the standard of services rendered. Pharmacists are the most accessible healthcare professional; thus they should possess good knowledge of malaria management in pediatrics. This study was designed to assess pharmacy students’ knowledge of malaria management in pediatrics. A cross-sectional survey among 140 pharmacy students of a Nigerian University, between July and August 2019, using a validated self-administered questionnaire. Data were summarized with descriptive statistics. Association between knowledge and year of study was determined using Chi-square, with p<0.05 considered significant. The majority (83.5 %) of the participants had good knowledge of the causes of malaria, while 43.6 % knew malaria could be transmitted to the unborn child by pregnant mothers. Most (65.0 %) knew that sulphadoxine-pyrimethamine is the drug of choice for IPTP, while 27.5 % of the respondents knew the frequency of its use during pregnancy. Half of the participants (50.7 %) are not knowledgeable of the symptoms of uncomplicated malaria. Thirty-one (22.1 %) knew ACT is recommended for all forms of uncomplicated malaria, and only 16.4% knew its dosage is based on weight not the age of the patient. Participants in the 5th year of study have significantly higher knowledge of relief of fever using a tepid sponge (P=0.011) and not recommending chloroquine as a first-line drug in malaria treatment in paediatric (P=0.018). The participants’ knowledge of causes and symptoms of malaria is poor and there is a substantial gap in their knowledge of pharmacotherapy of malaria in pediatrics. More clinical exposure of the students to the topic taught in classroom might improve their understanding.